On pseudo—optimal parameter choices and stopping rules for regularization methods in banach spaces. (December 2019) - Plato, R.; Hamarik, U.
Abstract : We consider generalized inverses and linear ill-posed problems in Banach spaces, and the concept of pseudo-optimal parameter choices and stopping rules for regularization methods is presented. The pseudo-optimality of the discrepancy principle for iterative methods like the Richardson iteration is shown, as well as the pseudo-optimality of different parameter choices for the iterated method of Lavrentiev.